Microstructure Evolution and Mechanical Property Variation in FE-MN-AL-C Low- density Steel during multiaxial forging: : Experimental and numerical Investigation - Kumar, Hemant (IIT(BHU) Varanasi, 2026)
Abstract is available in the attachment.
Keywords: Mechanical Engineering